KONSEP SAKINAH PADA PERNIKAHAN DINI DI DESA TAMANSARI KECAMATAN WULUHAN KABUPATEN JEMBER - Laily Nur Fadillah, Ahmad Zuhairus Zaman, (Mabahits : Jurnal Hukum Keluarga Islam, 2022)
Marriage ordained by God is a noble institution to regulate the relationship between men and women in accordance with human dignity. One of the goals of marriage is to realize a legitimate life based on mawaddah wa rahmah, namely a peaceful life based on love and affection between husband and wife and all family members. Early marriage is closely related to the absence of marriage readiness, such as readiness, readiness of property or material and physical readiness. The subjects in this study were the people of Tamansari Village, Kec. Wuluhan and a couple who had an early marriage. With the type of phenomenological research. This study resulted in: (1) the concept of Sakinah in the community, namely mutual acceptance, trust, and surrender of sustenance or sufficient economic origin to eat and go to school. (2) The application of the concept of sakinah to couples who have an early marriage in Tamansari Village, Wuluhan District, has harmony in principle, satisfaction for each partner and is open in any case without hope.